Small molecules in oncology - Martens, Uwe Marc (Recent results in cancer research, 2014)
Extensive research into the molecular mechanisms of cancer has heralded a new age of targeted therapy. The field of personalized cancer therapy is now growing rapidly, and the progress being made will result in significant changes in the treatment algorithms for cancer patients. Numerous novel targets that are crucial for the survival of cancer cells can be attacked by small molecules such as protein tyrosine kinase inhibitors. This book, written by acknowledged experts, discusses in detail the most recent developments in targeted cancer therapy using small molecules. A wide range of small molecules is covered, including, in addition to tyrosine kinase inhibitors, mTOR, proteasome, and multikinase inhibitors, among others. For each molecule, aspects such as chemical structure, mechanism of action, drug targets, drug interactions, preclinical studies, clinical trials, treatment applications, and toxicity are discussed
Description based upon print version of record
Keywords: Aufsatzsammlung; Kleines Molekül; Cytostatikum